DIGITAL MEDIA AND THE DIFFUSION OF FRUGAL LIVING: STRENGTHENING GENERATION Z’S FINANSIAL LITERACY - Indi Azzahra Ibtihal; Aprilianti Pratiwi (Laboratorium Ilmu Komunikasi Fisip UHO, 2026)
Generation Z in Indonesia faces a gap between financial inclusion and literacy, prompting them to seek more adaptive financial management strategies, including frugal living, which is popular through digital media. This study aims to analyze the stages of frugal living adoption and the role of digital media as a communication channel that shapes Generation Z's understanding and practice of frugal living. Using a descriptive qualitative method, data was obtained through in-depth interviews with four informants, namely three Generation Z individuals and one content creator. The analysis was conducted using the Miles & Huberman model based on Rogers' five stages of adoption. The results show that digital media serve as the main source of knowledge formation and reinterpretation of the concept of frugal living. The findings show that there are variations in adoption patterns, where early adopters internalize practices stably, the early majority implement strategies gradually and are more structured, while the late majority tend to be reactive and inconsistent. This study concludes that digital media plays a strategic role in facilitating the adoption process while strengthening Generation Z's financial literacy. The findings enrich the study of innovation diffusion and provide a basis for the development of more effective digital financial communications.